PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN HUTAN DESA DI NEGERI MORELLA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Iskar, Iskar; Silaya, Thomas; Rumra, Siti (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The purpose of this study was to find out the community perceptions of village forest management in Morella Country. The research method is descriptive qualitative. The sample was determined using a purposive sampling method which only focused on communities directly involved in Village Forest (HD) management with a total of 31 respondents and several figures as key informants. Data collection methods were carried out by means of observation, interviews and literature study. Data analysis used descriptive statistics with a Likert scale as the measurement scale, namely strongly agree (3), agree (2), disagree (1) with high, medium and low categorization for each value. The research results show that the community's perception of village forest management in Morella Country is classified in the 'Medium' category, including perceptions of pre-licensing village forest management, namely socialization and facilitation, formation of LPHD, technical verification and issuance of permits and post-licensing, namely HD planning and implementation..